# 3.5E: Exercises

- Page ID
- 17628

\( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \)

\( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)

This set contains exercises specifically identified by \Lex that ask you to implement the verification procedure. These particular exercises were chosen arbitrarily you can just as well formulate such laboratory problems for any of the equations in Exercises \((3.5E.1)\) to \((3.5E.10)\), \((3.5E.14)\) to \((3.5E.25)\), and \((3.5E.28)\) to \((3.5E.51)\).

In Exercises \((3.5E.1)\) to \((3.5E.10)\), find a fundamental set of Frobenius solutions. Compute \(a_0\), \(a_{1}\) \(\dots\), \(a_N\) for \(N\) at least \(7\) in each solution.

## Exercise \(\PageIndex{1}\)

\(2x^2(1+x+x^2)y''+x(3+3x+5x^2)y'-y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{2}\)

\(3x^2y''+2x(1+x-2x^2)y'+(2x-8x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{3}\)

\(x^2(3+3x+x^2)y''+x(5+8x+7x^2)y'-(1-2x-9x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{4}\)

\(4x^2y''+x(7+2x+4x^2)y'-(1-4x-7x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{5}\)

\(12x^2(1+x)y''+x(11+35x+3x^2)y'-(1-10x-5x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{6}\)

\(x^2(5+x+10x^2)y''+x(4+3x+48x^2)y'+(x+36x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{7}\)

\(8x^2y''-2x(3-4x-x^2)y'+(3+6x+x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{8}\)

\(18x^2(1+x)y''+3x(5+11x+x^2)y'-(1-2x-5x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{9}\)

\(x(3+x+x^2)y''+(4+x-x^2)y'+xy=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{10}\)

\(10x^2(1+x+2x^2)y''+x(13+13x+66x^2)y'-(1+4x+10x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{11}\)

\Lex

The Frobenius solutions of

\begin{eqnarray*}

2x^2(1+x+x^2)y''+x(9+11x+11x^2)y'+(6+10x+7x^2)y=0

\end{eqnarray*}

obtained in Example \((3.5.1)\) are defined on \((0,\rho)\), where \(\rho\) is defined in Theorem \((3.5.2)\). Find \(\rho\). Then do the following experiments for each Frobenius solution, with \(M=20\) and \(\delta=.5\rho\), \(.7\rho\), and \(.9\rho\) in the verification procedure described at the end of this section.

(a) Compute \(\sigma_N(\delta)\) (see Equation \((3.5.28)\)) for \(N=5\), \(10\), \(15\), \(\dots\), \(50\).

(b) Find \(N\) such that \(\sigma_N(\delta)<10^{-5}\).

(c) Find \(N\) such that \(\sigma_N(\delta)<10^{-10}\).

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{12}\)

\Lex

By Theorem \((3.5.2)\), the Frobenius solutions of the equation in Exercise \((3.5E.4)\) are defined on \((0,\infty)\). Do experiments (a), (b), and (c) of Exercise \((3.5E.11)\) for each Frobenius solution, with \(M=20\) and \(\delta=1\), \(2\), and \(3\) in the verification procedure described at the end of this section.

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{13}\)

\Lex

The Frobenius solutions of the equation in Exercise \((3.5E.6)\) are defined on \((0,\rho)\), where \(\rho\) is defined in Theorem \((3.5.2)\). Find \(\rho\) and do experiments (a), (b), and (c), of Exercise \((3.5E.11)\) for each Frobenius solution, with \(M=20\) and \(\delta=.3\rho\), \(.4\rho\), and \(.5\rho\), in the verification procedure described at the end of this section.

**Answer**-
Add texts here. Do not delete this text first.

In Exercises \9(3.5E.14)\) to \((3.5E.25)\), find a fundamental set of Frobenius solutions. Give explicit formulas for the coefficients in each solution.

## Exercise \(\PageIndex{14}\)

\(2x^2y''+x(3+2x)y'-(1-x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{15}\)

\(x^2(3+x)y''+x(5+4x)y'-(1-2x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{16}\)

\(2x^2y''+x(5+x)y'-(2-3x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{17}\)

\(3x^2y''+x(1+x)y'-y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{18}\)

\(x^2y''-xy'+(1-2x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{19}\)

\(9x^2y''+9xy'-(1+3x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{20}\)

\(3x^2y''+x(1+x)y'-(1+3x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{21}\)

\(2x^2(3+x)y''+x(1+5x)y'+(1+x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{22}\)

\(x^2(4+x)y''-x(1-3x)y'+y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{23}\)

\(2x^2y''+5xy'+(1+x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{24}\)

\(x^2(3+4x)y''+x(5+18x)y'-(1-12x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{25}\)

\(6x^2y''+x(10-x)y'-(2+x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{26}\)

\Lex

By Theorem \((3.5.2)\) the Frobenius solutions of the equation in Exercise \((3.5E.17)\) are defined on \((0,\infty)\). Do experiments (a), (b), and (c) of Exercise \((3.5E.11)\) for each Frobenius solution, with \(M=20\) and \(\delta=3\), \(6\), \(9\), and \(12\) in the verification procedure described at the end of this section.

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{27}\)

\Lex

The Frobenius solutions of the equation in Exercise \((3.5E.22)\) are defined on \((0,\rho)\), where \(\rho\) is defined in Theorem \((3.5.2)\). Find \(\rho\) and do experiments (a), (b), and (c) of Exercise \((3.5E.11)\) for each Frobenius solution, with \(M=20\) and \(\delta=.25\rho\), \(.5\rho\), and \(.75\rho\) in the verification procedure described at the end of this section.

**Answer**-
Add texts here. Do not delete this text first.

In Exercises \((3.5E.28)\) to \((3.5E.32)\), find a fundamental set of Frobenius solutions. Compute coefficients \(a_0\), \(\dots\), \(a_N\) for \(N\) at least \(7\) in each solution.

## Exercise \(\PageIndex{28}\)

\(x^2(8+x)y''+x(2+3x)y'+(1+x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{29}\)

\(x^2(3+4x)y''+x(11+4x)y'-(3+4x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{30}\)

\(2x^2(2+3x)y''+x(4+11x)y'-(1-x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{31}\)

\(x^2(2+x)y''+5x(1-x)y'-(2-8x)y\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{32}\)

\(x^2(6+x)y''+x(11+4x)y'+(1+2x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

In Exercises \((3.5E.33)\) to \((3.5E.46)\), find a fundamental set of Frobenius solutions. Give explicit formulas for the coefficients in each solution.

## Exercise \(\PageIndex{33}\)

\(8x^2y''+x(2+x^2)y'+y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{34}\)

\(8x^2(1-x^2)y''+2x(1-13x^2)y'+(1-9x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{35}\)

\(x^2(1+x^2)y''-2x(2-x^2)y'+4y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{36}\)

\(x(3+x^2)y''+(2-x^2)y'-8xy=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{37}\)

\(4x^2(1-x^2)y''+x(7-19x^2)y'-(1+14x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{38}\)

\(3x^2(2-x^2)y''+x(1-11x^2)y'+(1-5x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{39}\)

\(2x^2(2+x^2)y''-x(12-7x^2)y'+(7+3x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{40}\)

\(2x^2(2+x^2)y''+x(4+7x^2)y'-(1-3x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{41}\)

\(2x^2(1+2x^2)y''+5x(1+6x^2)y'-(2-40x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{42}\)

\(3x^2(1+x^2)y''+5x(1+x^2)y'-(1+5x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{43}\)

\(x(1+x^2)y''+(4+7x^2)y'+8xy=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{44}\)

\(x^2(2+x^2)y''+x(3+x^2)y'-y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{45}\)

\(2x^2(1+x^2)y''+x(3+8x^2)y'-(3-4x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{46}\)

\(9x^2y''+3x(3+x^2)y'-(1-5x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

In Exercises \((3.5E.47)\) to \((3.5E.51)\), find a fundamental set of Frobenius solutions. Compute the coefficients \(a_0\), \(\dots\), \(a_{2M}\) for \(M\) at least \(7\) in each solution.

## Exercise \(\PageIndex{47}\)

\(6x^2y''+x(1+6x^2)y'+(1+9x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{48}\)

\(x^2(8+x^2)y''+7x(2+x^2)y'-(2-9x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{49}\)

\(9x^2(1+x^2)y''+3x(3+13x^2)y'-(1-25x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{50}\)

\(4x^2(1+x^2)y''+4x(1+6x^2)y'-(1-25x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{51}\)

\(8x^2(1+2x^2)y''+2x(5+34x^2)y'-(1-30x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{52}\)

Suppose \(r_1>r_2\), \(a_0=b_0=1\), and the Frobenius series

\begin{eqnarray*}

y_1=x^{r_1}\sum_{n=0}^\infty a_nx^n\quad\mbox{ and } \quad y_2=x^{r_2}\sum_{n=0}^\infty b_nx^n

\end{eqnarray*}

both converge on an interval \((0,\rho)\).

(a) Show that \(y_1\) and \(y_2\) are linearly independent on \((0,\rho)\).

Hint: Show that if \(c_1\) and \(c_2\) are constants such that \(c_1y_1+c_2y_2\equiv0\) on \((0,\rho)\), then

\begin{eqnarray*}

c_1x^{r_1-r_2}\sum_{n=0}^\infty a_nx^n+ c_2\sum_{n=0}^\infty b_nx^n=0,\quad 0<x<\rho.

\end{eqnarray*}

Then let \(x\to0+\) to conclude that \(c_2=0\).

(b) Use the result of part (a) to complete the proof of Theorem \((3.5.3)\).

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{53}\)

The equation

\begin{equation}\label{eq:3.5E.1}

x^2y''+xy'+(x^2-\nu^2)y=0

\end{equation}

is Bessel's equation of order \(\nu\). (Here \(\nu\) is a parameter, and this use of "order'' should not be confused with its usual use as in "the order of the equation.'') The solutions of \eqref{eq:3.5E.1} are Bessel functions of order \(\nu\).

(a) Assuming that \(\nu\) isn't an integer, find a fundamental set of Frobenius solutions of \eqref{eq:3.5E.1}.

(b) If \(\nu=1/2\), the solutions of \eqref{eq:3.5E.1} reduce to familiar elementary functions. Identify these functions.

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{54}\)

(a) Verify that

\begin{eqnarray*}

{d\over dx}\left(|x|^rx^n\right)=(n+r)|x|^rx^{n-1} \quad \mbox{and} \quad {d^2\over dx^2}\left(|x|^rx^n\right)=(n+r)(n+r-1)|x|^rx^{n-2}

\end{eqnarray*}

if \(x\ne0\).

(b) Let

\begin{eqnarray*}

Ly= x^2(\alpha_0+\alpha_1x+\alpha_2x^2)y''+x(\beta_0+\beta_1x+\beta_2x^2)y' +(\gamma_0+\gamma_1x+\gamma_2x^2)y=0.

\end{eqnarray*}

Show that if \(x^r\sum_{n=0}^\infty a_nx^n\) is a solution of \(Ly=0\) on \((0,\rho)\) then \(|x|^r\sum_{n=0}^\infty a_nx^n\) is a solution on \((-\rho,0)\) and \((0,\rho)\).

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{55}\)

(a) Deduce from Equation \((3.5.20)\) that

\begin{eqnarray*}

a_n(r)=(-1)^n\prod_{j=1}^n{p_1(j+r-1)\over p_0(j+r)}.

\end{eqnarray*}

(b) Conclude that if \(p_0(r)=\alpha_0(r-r_1)(r-r_2)\) where \(r_1-r_2\) is not an integer, then

\begin{eqnarray*}

y_1=x^{r_1}\sum_{n=0}^\infty a_n(r_1)x^n\quad\mbox{ and }\quad y_2=x^{r_2}\sum_{n=0}^\infty a_n(r_2)x^n

\end{eqnarray*}

form a fundamental set of Frobenius solutions of

\begin{eqnarray*}

x^2(\alpha_0+\alpha_1x)y''+x(\beta_0+\beta_1x)y'+(\gamma_0+\gamma_1x)y=0.

\end{eqnarray*}

(c) Show that if \(p_0\) satisfies the hypotheses of part (b) then

\begin{eqnarray*}

y_1=x^{r_1}\sum_{n=0}^\infty {(-1)^n\over n!\prod_{j=1}^n(j+r_1-r_2)} \left(\gamma_1\over\alpha_0\right)^nx^n

\end{eqnarray*}

and

\begin{eqnarray*}

y_2=x^{r_2}\sum_{n=0}^\infty {(-1)^n\over n!\prod_{j=1}^n(j+r_2-r_1)} \left(\gamma_1\over\alpha_0\right)^nx^n

\end{eqnarray*}

form a fundamental set of Frobenius solutions of

\begin{eqnarray*}

\alpha_0x^2y''+\beta_0xy'+(\gamma_0+\gamma_1x)y=0.

\end{eqnarray*}

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{56}\)

Let

\begin{eqnarray*}

Ly=x^2(\alpha_0+\alpha_2x^2)y''+x(\beta_0+\beta_2x^2)y'+ (\gamma_0+\gamma_2x^2)y=0

\end{eqnarray*}

and define

\begin{eqnarray*}

p_0(r)=\alpha_0r(r-1)+\beta_0r+\gamma_0\quad\mbox{ and }\quad p_2(r)=\alpha_2r(r-1)+\beta_2r+\gamma_2.

\end{eqnarray*}

(a) Use Theorem \((3.5.2)\) to show that if

\begin{equation}\label{eq:3.5E.2}

\begin{array}{rcl}

a_0(r)&=&1,\\

p_0(2m+r)a_{2m}(r)+p_2(2m+r-2)a_{2m-2}(r)&=&0,\quad m\ge1,

\end{array}

\end{equation}

then the Frobenius series \(y(x,r)=x^r\sum_{m=0}^\infty a_{2m}x^{2m}\) satisfies \(Ly(x,r)=p_0(r)x^r\).

(b) Deduce from \eqref{eq:3.5E.2} that if \(p_0(2m+r)\) is nonzero for every positive integer \(m\) then

\begin{eqnarray*}

a_{2m}(r)=(-1)^m\prod_{j=1}^m{p_2(2j+r-2)\over p_0(2j+r)}.

\end{eqnarray*}

(c) Conclude that if \(p_0(r)=\alpha_0(r-r_1)(r-r_2)\) where \(r_1-r_2\) is not an even integer, then

\begin{eqnarray*}

y_1=x^{r_1}\sum_{m=0}^\infty a_{2m}(r_1)x^{2m}\quad\mbox{ and }\quad y_2=x^{r_2}\sum_{m=0}^\infty a_{2m}(r_2)x^{2m}

\end{eqnarray*}

form a fundamental set of Frobenius solutions of \(Ly=0\).

(d) Show that if \(p_0\) satisfies the hypotheses of part (c) then

\begin{eqnarray*}

y_1=x^{r_1}\sum_{m=0}^\infty {(-1)^m\over 2^mm!\prod_{j=1}^m(2j+r_1-r_2)} \left(\gamma_2\over\alpha_0\right)^mx^{2m}

\end{eqnarray*}

and

\begin{eqnarray*}

y_2=x^{r_2}\sum_{m=0}^\infty {(-1)^m\over 2^mm!\prod_{j=1}^m(2j+r_2-r_1)} \left(\gamma_2\over\alpha_0\right)^mx^{2m}

\end{eqnarray*}

form a fundamental set of Frobenius solutions of

\begin{eqnarray*}

\alpha_0x^2y''+\beta_0xy'+(\gamma_0+\gamma_2x^2)y=0.

\end{eqnarray*}

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{57}\)

Let

\begin{eqnarray*}

Ly=x^2q_0(x)y''+xq_1(x)y'+q_2(x)y,

\end{eqnarray*}

where

\begin{eqnarray*}

q_0(x)=\sum_{j=0}^\infty \alpha_jx^j,\quad q_1(x)=\sum_{j=0}^\infty \beta_jx^j,\quad q_2(x)=\sum_{j=0}^\infty \gamma_jx^j,

\end{eqnarray*}

and define

\begin{eqnarray*}

p_j(r)=\alpha_jr(r-1)+\beta_jr+\gamma_j,\quad j=0,1,\dots.

\end{eqnarray*}

Let \(y=x^r\sum_{n=0}^\infty a_nx^n\). Show that

\begin{eqnarray*}

Ly=x^r\sum_{n=0}^\infty b_nx^n,

\end{eqnarray*}

where

\begin{eqnarray*}

b_n=\sum_{j=0}^np_j(n+r-j)a_{n-j}.

\end{eqnarray*}

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{58}\)

(a) Let \(L\) be as in Exercise \((3.5E.57)\). Show that if

\begin{eqnarray*}

y(x,r)=x^r\sum_{n=0}^\infty a_n(r)x^n

\end{eqnarray*}

where

\begin{eqnarray*}

a_0(r)&=&1,\\

a_n(r)&=&-\displaystyle{1\over p_0(n+r)}\sum_{j=1}^n p_j(n+r-j)a_{n-j}(r),\quad n\ge1,

\end{eqnarray*}

then

\begin{eqnarray*}

Ly(x,r)=p_0(r)x^r.

\end{eqnarray*}

(b) Conclude that if

\begin{eqnarray*}

p_0(r)=\alpha_0(r-r_1)(r-r_2)

\end{eqnarray*}

where \(r_1-r_2\) isn't an integer then \(y_1=y(x,r_1)\) and \(y_2=y(x,r_2)\) are solutions of \(Ly=0\).

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{59}\)

Let

\begin{eqnarray*}

Ly=x^2(\alpha_0+\alpha_qx^q)y''+x(\beta_0+\beta_qx^q)y'+ (\gamma_0+\gamma_qx^q)y

\end{eqnarray*}

where \(q\) is a positive integer, and define

\begin{eqnarray*}

p_0(r)=\alpha_0r(r-1)+\beta_0r+\gamma_0\quad\mbox{ and }\quad p_q(r)=\alpha_qr(r-1)+\beta_qr+\gamma_q.

\end{eqnarray*}

(a) Show that if

\begin{eqnarray*}

y(x,r)=x^{r}\sum_{m=0}^\infty a_{qm}(r)x^{qm}

\end{eqnarray*}

where

\begin{equation}\label{eq:3.5E.3}

\begin{array}{rcl}

a_0(r)&=&1,\\

a_{qm}(r)&=&-\displaystyle{p_q\left(q(m-1)+r\right)\over p_0(qm+r)}a_{q(m-1)}(r),\quad m\ge1,

\end{array}

\end{equation}

then

\begin{eqnarray*}

Ly(x,r)=p_0(r)x^r.

\end{eqnarray*}

(b) Deduce from \eqref{eq:3.5E.3} that

\begin{eqnarray*}

a_{qm}(r)=(-1)^m\prod_{j=1}^m{p_q\left(q(j-1)+r\right)\over p_0(qj+r)}.

\end{eqnarray*}

(c) Conclude that if \(p_0(r)=\alpha_0(r-r_1)(r-r_2)\) where \(r_1-r_2\) is not an integer multiple of \(q\), then

\begin{eqnarray*}

y_1=x^{r_1}\sum_{m=0}^\infty a_{qm}(r_1)x^{qm}\quad\mbox{ and }\quad y_2=x^{r_2}\sum_{m=0}^\infty a_{qm}(r_2)x^{qm}

\end{eqnarray*}

form a fundamental set of Frobenius solutions of \(Ly=0\).

(d) Show that if \(p_0\) satisfies the hypotheses of part (c) then

\begin{eqnarray*}

y_1=x^{r_1}\sum_{m=0}^\infty {(-1)^m\over q^mm!\prod_{j=1}^m(qj+r_1-r_2)} \left(\gamma_q\over\alpha_0\right)^mx^{qm}

\end{eqnarray*}

and

\begin{eqnarray*}

y_2=x^{r_2}\sum_{m=0}^\infty {(-1)^m\over q^mm!\prod_{j=1}^m(qj+r_2-r_1)} \left(\gamma_q\over\alpha_0\right)^mx^{qm}

\end{eqnarray*}

form a fundamental set of Frobenius solutions of

\begin{eqnarray*}

\alpha_0x^2y''+\beta_0xy'+(\gamma_0+\gamma_qx^q)y=0.

\end{eqnarray*}

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{60}\)

(a) Suppose \(\alpha_0,\alpha_1\), and \(\alpha_2\) are real numbers with \(\alpha_0\ne0\), and \(\{a_n\}_{n=0}^\infty\) is defined by

\begin{eqnarray*}

\alpha_0a_1+\alpha_1a_0=0

\end{eqnarray*}

and

\begin{eqnarray*}

\alpha_0a_n+\alpha_1a_{n-1}+\alpha_2a_{n-2}=0,\quad n\ge2.

\end{eqnarray*}

Show that

\begin{eqnarray*}

(\alpha_0+\alpha_1x+\alpha_2x^2)\sum_{n=0}^\infty a_nx^n=\alpha_0a_0,

\end{eqnarray*}

and infer that

\begin{eqnarray*}

\sum_{n=0}^\infty a_nx^n={\alpha_0a_0\over\alpha_0+\alpha_1x+\alpha_2x^2}.

\end{eqnarray*}

(b) With \(\alpha_0,\alpha_1\), and \(\alpha_2\) as in part (a), consider the equation

\begin{equation}\label{eq:3.5E.4}

x^2(\alpha_0+\alpha_1x+\alpha_2 x^2)y''+x(\beta_0+\beta_1x+\beta_2x^2)y'+ (\gamma_0+\gamma_1x+\gamma_2x^2)y=0,

\end{equation}

and define

\begin{eqnarray*}

p_j(r)=\alpha_jr(r-1)+\beta_jr+\gamma_j,\quad j=0,1,2.

\end{eqnarray*}

Suppose

\begin{eqnarray*}

{p_1(r-1)\over p_0(r)}= {\alpha_1\over\alpha_0},\qquad {p_2(r-2)\over p_0(r)}= {\alpha_2\over\alpha_0},

\end{eqnarray*}

and

\begin{eqnarray*}

p_0(r)=\alpha_0(r-r_1)(r-r_2),

\end{eqnarray*}

where \(r_1>r_2\). Show that

\begin{eqnarray*}

y_1={x^{r_1}\over\alpha_0+\alpha_1x+\alpha_2x^2}\quad\mbox{ and }\quad y_2={x^{r_2}\over\alpha_0+\alpha_1x+\alpha_2x^2}

\end{eqnarray*}

form a fundamental set of Frobenius solutions of \eqref{eq:3.5E.4} on any interval \((0,\rho)\) on which \(\alpha_0+\alpha_1x+\alpha_2x^2\) has no zeros.

**Answer**-
Add texts here. Do not delete this text first.

In Exercises \((3.5E.61)\) to \((3.5E.68)\), use the method suggested by Exercise \((3.5E.60)\) to find the general solution on some interval \((0,\rho)\).

## Exercise \(\PageIndex{61}\)

\(2x^2(1+x)y''-x(1-3x)y'+y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{62}\)

\(6x^2(1+2x^2)y''+x(1+50x^2)y'+(1+30x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{63}\)

\(28x^2(1-3x)y''-7x(5+9x)y'+7(2+9x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{64}\)

\(9x^2(5+x)y''+9x(5+3x)y'-(5-8x)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{65}\)

\(8x^2(2-x^2)y''+2x(10-21x^2)y'-(2+35x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{66}\)

\(4x^2(1+3x+x^2)y''-4x(1-3x-3x^2)y'+3(1-x+x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{67}\)

\(3x^2(1+x)^2y''-x(1-10x-11x^2)y'+(1+5x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.

## Exercise \(\PageIndex{68}\)

\(4x^2(3+2x+x^2)y''-x(3-14x-15x^2)y'+(3+7x^2)y=0\)

**Answer**-
Add texts here. Do not delete this text first.